Carl Larsson läser Anna Maria Lenngren utan literary transfer: Om litterär kompetens och personlig läsning - Torell, Örjan (Tidskrift för litteraturvetenskap, 2013)
Carl Larsson Reading Anna Maria Lenngren without ”Literary Transfer”. On ”Literary Competence” and ”Personal Reading” Reading literature, we relate the fictive life we encounter to our own. That mechanism is called ”literary transfer”. The concept was introduced in the 1970’s, but dates back to classical rhetoric, where it is known as subtilitas applicandi. ”Literary transfer” is also an equivalent to Louise Rosenblatt’s concept of ”aesthetic stance”, which concerns the personal aspects of reading theory. Inspired by Mikhail Bakhtin and his understanding of literature as a very personal form of dialogue, I see ”literary transfer” as a fundamental aspect of literary competence that deserves further exploration. My article opens with an attempt to show with visual clarity the potential and function of ”literary transfer” and personal reading. To this end, one of Carl Larsson’s illustrations for an 1884 edition of Anna Maria Lenngren’s poems is classified as a literary reading without ”transfer”, whereas an example of his later Sundborn art is shown to be, in principle, a work of ”transfer”-art. I then demonstrate some misunderstandings in the field of personal reading, and suggest that they are the typical and systematic results of a dichotomised model of thinking that views personal reading as something principally alien – or even hostile – to literary competence.